KANDUNGAN BAKTERI PATOGEN PADA UDANG WINDU (Penaeus monodon Fabricius) PASCAPANEN ASAL TAMBAK - Andi Noor Asikin; S Hutabarat; Ys Darmanto; S Budi Prayitno (UIR Press, 2014)
The purpose of this study was to know the pathogenic bacteria contamination on prawn post-harvested after being handled by fisherman and collectors and to study the bacterial contaminants in salty water pond as media cultivation and water process as well as ice cubes used by fisherman and collectors. Research carried out during three months at the communities’ salty water ponds in the Sub Districts of Muara Jawa, Anggana, and Muara Badak of Kutai Kartanegara Regency. The materials used consisted of tiger prawn (P. monodon F.) at the harvested age of 40-45 pieces/kg size, ice cubes, clean water, pond salty water, process water, and materials for microbial analysis. Sampling is also done on salty water pond, process water, and ice. Each sample taken was repeated three times. Analysis methods used to determine the Total Plate Count (TPC) is based on SNI 01-2339-1991. To measure the pathogenic bacteria at shrimp, salty pond water, process water, and ice cubes consisted of ​​Escherchia coli bacteria, was based on the SNI 01-2332-1991 method, Salmonella is based on the SNI 01-2335-1991 method, and Vibrio cholerae is based on the SNI 01-2341-1991 method. Data were then further tabulated and analyzed descriptively. The results indicated that E. coli bacteria only found at prawns, process water, and salty pond water from Muara Jawa Sub District, while in other Sub Districts of Muara Badak and Anggana were not found.